(untitled) (UNED Research Journal, 2024)
Introduction: Outdoor garbage disposal and accumulation sites concentrate water, soil and atmospheric pollution; however, there is little information on this problem in Ecuador. Objective: Assess the environmental impact, including methane emissions, from the open-air garbage dump in Naranjito, Ecuador. Methods: To determine the methane emission rate from solid waste biomass, we applied the static camera method, with a portable device, for 15 continuous days (May-June 2023) and at 08:00, 12:30 and 16:00. For the qualitative evaluation of environmental impact, we used the Global Index weighting, based on the impacts generated in the physical and perceptual environment. Results: The global Index was 53,3, i.e. critical impact; mean emission rate was 858,8mg/m2/h, higher than the emission rate of the surrounding soil (133,4mg/m2/h; p<0,05). Conclusion: A sustainable management alternative is urgent to reduce the methane emission rate in Naranjito.